Heterologous laccase from the marine environment: Purification, characterization, and degradation of synthetic dyes - Otero, Igor Vinicius Ramos [UNESP] (2025)
The marine-derived fungus Peniophora sp. CBMAI 1063 is a hyper-producer of laccase. Laccases are multicopper oxidases able to oxidize different aromatic compounds while reducing molecular oxygen to water. Several laccases from terrestrial environments have been purified and characterized. However, little is known about marine-derived laccases. In this study, Pnh_Lac1 (Lac1) from the fungus Peniophora sp. CBMAI 1063 was heterologously expressed in Pichia pastoris, purified, characterized, and used for the degradation/detoxification of synthetic dyes. Lac1 (∼72 kDa) exhibited optimal activity at 60 °C and pH 3, with good thermostability (T501h = 56 °C) and high tolerance to metal ions and organic solvents. Lac 1 decolorized/degraded different classes of dyes, under low enzyme concentrations (0.2–0.02 U mL-1), with an excellent performance regarding the decolorization of Indigo Carmine (93% after 2 h) in the presence of syringaldehyde. Additionally, 65% of the azo dye Reactive Black 5 was degraded by the Lac1-mediator system into lower molecular weight metabolites, with a significant reduction in phytotoxicity. These results demonstrate that the marine-derived Lac1 is a fungal laccase highly active under low concentration, with the potential to mitigate environmental pollutants on biodegradation strategies based on biocatalysis.